PERLINDUNGAN HUKUM ATAS PEMBATALAN ORDER PEMBELIAN MAKANAN SECARA SEPIHAK OLEH KONSUMEN MELALUI LAYANAN GO-FOOD PADA APLIKASI GO-JEK - Lisa Novalia Cuyana; Hayatul Ismi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
GOJEK is a social soul technology company that aims to improve the welfare of works in various informal sector in Indonesia. GOJEK which is an online based transportation developed by PT.GOJEK Indonesia has several services or features, one of which is GO-FOOD. GO-FOOD service in the GOJEK application is a food delivery service in which an agreement between the service provider and the costumer occurs. PT.GOJEK Indonesia through its system in the GOJEK application can bring together costumer as food order with drivers and carries.This type of research can be classified in the type of research that sosiological, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. The study was conducted at the Land Transportation Management Area IV in Riau Province and Riau Island Province and Basecamp GOJEK Banten Pekanbaru City, while the population and the sample are all parties related to the problems axamined in this study, the sources of the date used, primary, secondary and tertiary, than the collection in this study by interviews and library study.From the result of the research problem there are two main things that are concluded. First, legal protection for unilateral cancellation of orders in accordance with Article 1338 of the Civil Code regarding freedom of contract and Law Number 11 of 2008 concerning information and electronic transaction. Where in this provision it is in accordance with the application GO-JEK that the driver and consumer have made an agreement through electronic transaction as outlined in the electronic contract binding the parties. Secondly, due to the law arising from unilateral cancellation carried out by consumers based on Article 1365 regarding acts against the law, consumers are required to make compensation for actions taken against the driver who has suffered losses.Keywords: Legal Protection, Driver, Unilateral Cancellation